Out in the union : a labor history of queer America - Frank, Miriam (Temple University Press, 2014)
"Out in the Union tells the continuous story of queer American workers from the mid-1960s through 2013. Miriam Frank shrewdly chronicles the evolution of labor politics with queer activism and identity formation, showing how unions began affirming the rights of lesbian, gay, bisexual, and transgender workers in the 1970s and 1980s. She documents coming out on the job and in the union as well as issues of discrimination and harassment, and the creation of alliances between unions and LGBT communities. Featuring in-depth interviews with LGBT and labor activists, Frank provides an inclusive history of the convergence of labor and LGBT interests. She carefully details how queer caucuses in local unions introduced domestic partner benefits and union-based AIDS education for health care workers--innovations that have been influential across the U.S. workforce. Out in the Union also examines organizing drives at queer workplaces, campaigns for marriage equality, and other gay civil rights issues to show the enduring power of LGBT workers."--